IMPACT OF MARRIAGE UNDER CHILDREN IN THE PERSPECTIVE OF MARRIAGE LAW AND THE CIVIL CODE - Rudolf Johanes Hasoloan; Azril Rozzaqi (Indonesia Private Law Review, 2022)
Marriage represents both an emotional and formal commitment between two individuals, essential for the social and legal aspects of family life. In contemporary society, early marriages often lead to negative legal consequences. This research aims to examine the impact of early marriage in the context of the Marriage Law and the Civil Code. Employing a normative juridical research methodology, the research utilizes library research, drawing on a range of sources including legal texts, books, notes, and journals. The findings reveal that underage marriages have significant negative impacts. Judges frequently grant marriage dispensation applications for minors to mitigate potential severe consequences. The state has established age limits for marriage to address and manage issues arising from such unions. Early marriage can lead to social and legal problems for children, highlighting the importance of adhering to the legal regulations governing marriage.